2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091056
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of a neural-machine interface for artificial legs using prior knowledge of walking environment

Abstract: A previously developed neural-machine interface (NMI) based on neuromuscular-mechanical fusion has showed promise for recognizing user locomotion modes; however, errors of NMI during mode transitions were observed, which may challenge its real application. This study aimed to investigate whether or not the prior knowledge of walking environment could further improve the NMI performance. Linear Discriminant Analysis (LDA)-based classifiers were designed to identify user intent based on electromyographic (EMG) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Inspired by previous work (Du et al, 2012; Huang et al, 2011; Khademi and Simon, 2019; Liu et al, 2016; Wang et al, 2013), the hierarchical labelling architecture included both static (S) and transition (T) states. A static state describes an environment where an exoskeleton or prosthesis user would continuously perform the same locomotion mode (e.g., only level-ground terrain).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by previous work (Du et al, 2012; Huang et al, 2011; Khademi and Simon, 2019; Liu et al, 2016; Wang et al, 2013), the hierarchical labelling architecture included both static (S) and transition (T) states. A static state describes an environment where an exoskeleton or prosthesis user would continuously perform the same locomotion mode (e.g., only level-ground terrain).…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers have combined mechanical sensors with surface EMG for automated locomotion mode recognition. Such neuromuscular-mechanical data fusion has improved the locomotion mode recognition accuracies and decision times compared to implementing either system individually (Du et al, 2012; Huang et al, 2011; Liu et al, 2016; Wang et al, 2013). However, these measurements are still patient-dependent, and surface EMG are susceptible to fatigue, changes in electrode-skin conductivity, and crosstalk from adjacent muscles (Tucker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have combined mechanical sensors with surface EMG for automated locomotion mode recognition. Such neuromuscular-mechanical data fusion has improved the locomotion mode recognition accuracies and decision times compared to implementing either system individually (Huang et al, 2011;Du et al, 2012;Wang et al, 2013;Liu et al, 2016). However, these measurements are still patient-dependent, and surface EMG are susceptible to fatigue, changes in electrode-skin conductivity, and crosstalk from adjacent muscles (Tucker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Environment sensing could also be used to adapt low-level reference trajectories (e.g., changing toe clearance corresponding to an obstacle height) (Zhang et al, 2020) and optimal path planning (e.g., identifying opportunities for energy regeneration) (Laschowski et al, 2019a(Laschowski et al, , 2020a. Preliminary research has shown that supplementing an automated locomotion mode recognition system with environment information can improve the classification accuracies and decision times compared to excluding terrain information (Huang et al, 2011;Wang et al, 2013;Liu et al, 2016). Several researchers have explored using radar detectors (Kleiner et al, 2018) and laser rangefinders (Zhang et al, 2011;Wang et al, 2013;Liu et al, 2016) for environment sensing.…”
Section: Introductionmentioning
confidence: 99%